Interaction Between BGLF2 and BBLF1 Is Required for the Efficient Production of Infectious Epstein–Barr Virus Particles - Hung, Chien-Hui; Chiu, Ya-Fang; Wang, Wen-Hung; Chen, Lee-Wen; Chang, Pey-Jium; Huang, Tsung-Yu; Lin, Ying-Ju; Tsai, Wan-Ju; Yang, Chia-Ching (Frontiers in Microbiology, 2020)
BGLF2 is a tegument protein of the Epstein-Barr virus (EBV). This study finds that BGLF2 is expressed in the late stage of the EBV lytic cycle. Microscopic investigations reveal that BGLF2 is present in both the nucleus and the cytoplasm, and colocalized with BBLF1 and gp350 at juxtanuclear regions in the cytoplasm. This study also finds that the basic KKK69 motif of BGLF2 and acidic DYEE31 motif of BBLF1 are crucial for the interaction between BGLF2 and BBLF1, which is required for the recruitment of BGLF2 to the BBLF1 that is anchored on the trans Golgi-network (TGN). In addition, BGLF2 in a density gradient is co-sedimented with un-enveloped capsids, revealing that BGLF2 associates with the EBV capsid before the final envelopment. The knockout of BGLF2 expression is demonstrated to reduce the numbers of infectious virions that are released into the culture medium, but they do not affect the expression of lytic proteins and viral DNA replication. The production of infectious viral particles by a BGLF2-knockout mutant can be rescued by exogenously expressed BGLF2, but only partially rescued by BGLF2-3KA, which is a mutant with reduced ability to interact with BBLF1 but does not affect its ability to activate the MAPK pathway and the expression of the EBV lytic proteins, suggesting that the interaction of BGLF2 with BBLF1 is important to the efficient production of infectious viral particles during the maturation. The results of​ this study improve our understanding of how BGLF2 promotes EBV viral production.